2012
DOI: 10.1155/2012/318032
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Thermodynamics and Distributions Time to Achieve a Given Level of a Stochastic Process for Energy of System

Abstract: In a previous paper (Ryazanov (2011)) with the joint statistical distribution for the energy and lifetime (time to achieve a given level of a stochastic process for energy of system) to derive thermodynamic relationships, clarifying similar expressions of extended irreversible thermodynamics we used an exponential distribution of lifetime. In this paper, we explore a more realistic expression for the distribution of time to achieve a given level of a stochastic process for energy of system (or relaxation times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The object of further investigation will be the cluster of a liquid phase which is dense and compact contrast to a vapor phase. So, we will omit the index , use ] instead of , and speak about chemical potentials instead of differences in chemical potentials 5 .…”
Section: Mean Chemical Potentials In Different Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The object of further investigation will be the cluster of a liquid phase which is dense and compact contrast to a vapor phase. So, we will omit the index , use ] instead of , and speak about chemical potentials instead of differences in chemical potentials 5 .…”
Section: Mean Chemical Potentials In Different Modelsmentioning
confidence: 99%
“…The importance of nucleation initiates investigations from Wilson's experiments [1][2][3] up to modern investigations. Thermodynamic aspects of investigations occupy an important place in this field considering not only the fundamental question of stationarity (see to clarify it, e.g., [4,5]), but also the problems of smallness of characteristic embryos and corrections appeared because of its sizes and shapes [6]. The results given by thermodynamics immediately lead to quantitative description of kinetics [7] and can be included into consideration of some rather complex aggregates with very specific properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…But below we consider the stationary case, for which relations (2)-( 5) are satisfied with a certain approximation. A consideration of the general non-stationary case using queuing theory is given in [38][39][40]. In [39] it is shown that the argument s from ( 2)-( 3), ( 5) is written as a function of s, the argument is replaced, s→D(α=s)=f(s)~exp(-U/kBTe).…”
Section: Change In Rv Lifetime Under Irradiationmentioning
confidence: 99%
“…A consideration of the general non-stationary case using queuing theory is given in [38][39][40]. In [39] it is shown that the argument s from ( 2)-( 3), ( 5) is written as a function of s, the argument is replaced, s→D(α=s)=f(s)~exp(-U/kBTe). The function Q(s) from ( 2)-( 5) turns out to be a function of the form Q[D(α)], U is the additional potential energy received by the system, kB is the Boltzmann constant, Te is the absolute temperature.…”
Section: Change In Rv Lifetime Under Irradiationmentioning
confidence: 99%